Value cocreation in health - Nnabuko, Uchenna Chioma (The University of Edinburgh, 2021)
A shift in the focus of healthcare from diseases and treatment to wellness and prevention has contributed to the widespread acceptance and commitment to adopt preventive healthcare practices – including preventive health applications (apps) and devices. The aim of these apps and devices is to equip the user with information about their health to enable them to make better lifestyle choices that will positively impact their health in the long run. However, the use of these preventive health apps and devices is pervaded by a high user dropout rate. This draws attention to the way these technologies are designed. Recently, design frameworks for technology taking account of the values of users have arisen. These surface value explicitly and enable the use of value to incentivise action on the part of users towards prevention. Improvements in the effectiveness and efficiency of such frameworks offer new opportunities to use value to achieve behavioural change. As healthcare delivery and management becomes increasingly digital and used by highly diverse populations, understanding the role of value as an incentive gains importance. Many attempts at digitalisation of healthcare systems (particularly when we try to do things at scale) have failed and one potential reason for this is the different (and often competing) value systems of the stakeholders and different notions of value they use to judge and motivate use of the system. This thesis addresses value and value systems as a key factor in the development of healthcare systems and investigates how such an approach could be taken. Taking Value Sensitive Design (VSD) as a starting point, we analyse the role of stakeholder value. Motivated by our empirical experience we extend VSD to take account of the emergence of value through interaction. The main contributions of this thesis are: (a) The empirical analysis of a large-scale pilot on the adoption of wearable health technology and (b) motivated by this empirical analysis, the development of the Value Cocreation Design (VCD) framework (an extension of the VSD framework). VCD is a novel model that shifts the design focus from creating value to cocreating value. VCD focuses on the services that actors exchange in order to identify value in contrast with VSD that uses a predefined framework of values that the designer expects users to hold. The VCD framework is validated using empirical evidence obtained from the Berkshire Wearable Technology Pilot study. We also evaluate VCD by applying it to the Berkshire Wearable Technology Pilot. This exemplifies its application in a real-life design scenario
Keywords: value; wearable devices; value cocreation design; health